Asian Ambrosia Beetle, Granulate Ambrosia Beetle (no official common name), Xylosandrus crassiusculus (Motschulsky) (Insecta: Coleoptera: Scolytidae) - Thomas H. Atkinson; John L. Foltz; Robert C. Wilkinson; Russell F. Mizell, III (EDIS)
This document is EENY-131 (originally published as DPI Entomology Circular No. 310), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2000. Revised: June 2000.